2012
DOI: 10.1002/ejic.201200075
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Chemistry of Cu2+–tren Complexes Revisited: Exploring the Role of Species That Are Not Trigonal Bipyramidal

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…The kinetic data in the present work indicate that the previously detected structural reorganization of Cu 2+ between different pentacoordinate geometries [30,[49][50][51] are also possible with more complicated receptors. Moreover, the different behavior detected for the L1 and L2 ligands indicates that subtle changes in the nature of the ligand can lead to drastic changes in the chemical behavior.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The kinetic data in the present work indicate that the previously detected structural reorganization of Cu 2+ between different pentacoordinate geometries [30,[49][50][51] are also possible with more complicated receptors. Moreover, the different behavior detected for the L1 and L2 ligands indicates that subtle changes in the nature of the ligand can lead to drastic changes in the chemical behavior.…”
Section: Resultssupporting
confidence: 67%
“…In previous papers we have found that the combination of theoretical studies with experimental information is very useful to understand structural reorganizations between sp and tbp geometries in macrocyclic copper complexes [30,[49][50][51]. For that reason, and despite the very complex nature of the present systems hinders a detailed theoretical study, we decided to carry out some DFT and TD-DFT calculations aimed to analyze the possible coordination modes of Cu 2+ coordinated to L1 and L2, as well as obtaining the corresponding calculated spectra in order to compare them with the experimental results.…”
Section: The Kinetics Of Formation Of Mono-and Binuclear Cu 2+ -L1 Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination geometries of the five-coordinated complexes can be discussed using the τ-value, 21 which can be calculated by τ = (α − β)/60, where α and β denominate the largest and the second-largest angles around the metal center, respectively. Complexes with τ = 0 adopt an ideal square-pyramidal geometry, while those with τ = 1 adopt a nondistorted trigonal-bipyramidal geometry.…”
Section: Resultsmentioning
confidence: 90%
“…Metalloprism 6 shows four‐line hyperfine structure at 77 K, corresponding to the Δ m s =1 transition. Neither the Δ m s =2 transition nor complete delocalization of the unpaired electron was detected, and hence this is a case of noncommunicating copper(II) dimers in a square‐pyramidal environment ( g || >2.1> g ⊥ >2.00, and A || =148×10 −4 cm −1 ; Supporting Information, Figure S10) …”
Section: Resultsmentioning
confidence: 99%